Taxonomic review of the genus Phylloporia (Hymenochaetaceae, Basidiomycota) in Cuba - Castro Hernández, Lázaro; Camino Vilaró, Mayra; Herrera Figueroa, Sara (Instituto de Ecología, A.C., 2023)
Background and Aims: The genus Phylloporia is morphologically diverse and includes species which develop in restricted areas that are predominantly tropical and that have or do not have substrate specificity. Five species were reported for Cuba, however, due to the heterogeneity of the island’s ecosystems and the diversity of the genus, it is estimated that the number of taxa present is higher than that recorded. Therefore, the present work had as objective the taxonomic review of the genus Phylloporia in Cuba, based on the morphological analysis of specimens from Cuban herbaria. Methods: Specimens deposited in the mycological collections of the herbaria HAJB, of the National Botanical Garden, and HAC, of the Instituto de Ecología y Sistemática de Cuba were reviewed. The specimens were studied, described and determined macroscopically and microscopically with the support of specialized literature. Key results: Eight species of the genus Phylloporia were determined for Cuba: P. chrysites, P. fruticum, P. pectinata, and P. spathulata (previously recorded); P. verae-crucis (as a new record for the country); P. subpectinata (proposed as a new combination); P. pinarensis and P. rodriguezii (as two species new to science). Descriptions of their macroscopic and microscopic structures are given for these taxa. In addition, a distribution map of the treated species and a dichotomous key for the identification of the members of the genus in the national territory, which includes P. crystallina, that is a taxon not found in this study, are presented. Conclusions: The geographical distribution area of the known species of the genus in Cuba is expanded and new taxa are incorporated into the country’s mycobiota. However, it is necessary to increase sampling in areas where information gaps exist or are poorly explored, as well as in sites with high plant endemism. It is also necessary to implement molecular analyses in order to evaluate the phylogenetic relationships between the treated species and others of the genus and family.